Strategi Percepatan Kemandirian Keuangan Badan Layanan Umum Daerah RSUD Sidoarjo Barat - Amelia Indah Mawarni; Byba Melda; Prima Dewi Kusumawati; Andi Hayyun Abiddin (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Unstable income, low Cost Recovery Rate, and high budget subsidies from the Regional Budget/National Budget are challenges faced by the West Sidoarjo Regional General Hospital, which disrupt health services. The purpose of this study is to explore the strategies implemented by the West Sidoarjo Regional General Hospital using the Balanced Scored Card. The research design employs a qualitative case study approach, utilizing a purposive sampling technique. The number of samples is 16 respondents, consisting of 12 main informants and 4 triangulator informants. The analysis was carried out using qualitative analysis based on the Balanced Scorecard, employing a 4-perspective approach: the Financial Perspective, Customer Perspective, Internal Business Perspective, and Learning and Growth Perspective. The results of the study show that the greatest weight in the strategy to accelerate financial independence is the customer perspective. The customer perspective describes the trend of increasing patient visits caused by the opening of new services, patient satisfaction with services, and the closure of competing hospitals for BPJS services. The Internal Business Perspective describes business growth from the health and non-health sectors such as asset optimization, cooperation, and acceptance of educational services. The learning and growth perspective describes the BERAKHLAK culture that has been implemented by employees, increasing employee competency through internal and external training, increasing work motivation through reward and punishment and support from the APBD budget for training. RSUD Sidoarjo Barat is not yet financially independent due to insufficient income to finance operational expenses. RSUD Sidoarjo has only been operational for 3 years; the health services that have been opened are not yet optimal, patient visits are still unstable, dependence on BPJS patients and inefficient financial management. Acceleration strategies in increasing BLUD's financial independence with service diversification, budget efficiency, asset optimization, promotion, and cooperation. Keywords : Regional Public Service Agency, Balance Scored Card, Cost Recovery Rate, Financial Independence, Revenue.    ABSTRAK Pendapatan yang belum stabil, Cost Recovery Rate rendah dan tingginya subsidi anggaran dari APBD/APBN menjadi tantangan yang dihadapi RSUD Sidoarjo Barat yang menyebabkan terganggunya pelayanan kesehatan. Tujuan penelitian ini adalah mengeksplore strategi yang dilakukan RSUD Sidoarjo Barat menggunakann Balanced Scored Card. Desain penelitian  menggunakan kualitatif  pendekatan studi kasus dengan teknik purposive sampling. Jumlah sampel sebanyak 16 responden, terdiri dari 12 informan utama dan 4 informan triangulator. Analisa dilakukan dengan analisis kualitatif berdasarkan Balanced Score Card menggunakan pendekatan 4 perspektif yaitu Perspektif Keuangan, Perspektif Pelanggan, Perspektif Bisnis Internal dan Perspektif Pembelajaran dan Pertumbuhan. Hasil penelitian menunjukkan bobot terbesar dalam strategi percepatan kemandirian keuangan adalah prespektif pelanggan. Perspektif pelanggan menggambarkan trend kenaikan kunjungan pasien yang disebabkan pembukaan layanan baru, kepuasan pasien atas layanan dan ditutupnya rumah sakit pesaing atas layanan BPJS. Perspektif Bisnis Internal menggambarkan pertumbuhan bisnis dari sektor kesehatan dan non kesehatan seperti optimalisasi aset, kerjasama dan penerimaan layanan pendidikan. Perspektif pembelajaran dan pertumbuhan menggambarkan budaya BERAKHLAK yang sudah diimplementasikan oleh pegawai, peningkatan kompetensi pegawai melalui pelatihan internal eksternal, peningkatan motivasi kerja melalui reward punishment dan dukungan anggaran APBD untuk pelatihan. RSUD Sidoarjo Barat belum mandiri secara keuangan yang disebabkan belum tercukupinya pendapatan untuk pembiayaan belanja operasioan, RSUD Sidoarjo masih 3 tahun beroperasional, belum optimalnya layanan kesehatan yang dibuka, masih belum stabilnya kunjungan pasien, ketergantungan pada pasien BPJS dan manajemen keuangan yang belum efisien. Strategi percepatan dalam meningkatkan kemandirian keuangan BLUD dengan diversifikasi layanan, efisiensi anggaran, optimalisasi aset, promosi dan kerjasama. Kata Kunci: Badan Layanan Umum Daerah, Balance Scored Card, Cost Recovery Rate, Kemandirian Keuangan, Pendapatan.